Deformation behaviour of [001] oriented MgO using combined in-situ nano-indentation and micro-Laue diffraction - Bhowmik,A; Britton,TB; Lee,J; Liu,W; Jun,T-S; Sernicola,G; Karimpour,M; Balint,D; Giuliani,F (Acta Materialia, 2018)
We report a coupled in-situ micro-Laue diffraction and nano-indentation experiment, with spatial and time resolution, to investigate the deformation mechanisms in [001]-oriented single crystal MgO. Crystal plasticity finite element modelling was applied to aid interpretation of the experimental observations of plasticity. The Laue spots showed both rotation and streaking upon indentation that is typically indicative of both elastic lattice rotation and plastic strain gradients respectively in the material. Multiple facets of streaking of the Laue peaks suggested plastic slip occurring on almost all the {101}-type slip planes oriented 45° to the sample surface with no indication of slip on the 90° {110} planes. Crystal plasticity modelling also supported these experimental observations. Owing to asymmetric slip beneath the indenter, as predicted by modelling results and observed through Laue analysis, sub-grains were found to nucleate with distinct misorientation. With cyclic loading, the mechanical hysteresis behaviour in MgO is revealed through the changing profiles of the Laue reflections, driven by reversal of plastic strain by the stored elastic energy. Crystal plasticity simulations have also shown explicitly that in subsequent loading cycles after first, the secondary slip system unloads completely elastically while some plastic strain of the primary slip reverses. Tracking the Laue peak movement, a higher degree of lattice rotation was seen to occur in the material under the indent, which gradually decreased moving laterally away. With the progress of deformation, the full field elastic strain and rotation gradients were also constructed which showed opposite lattice rotations on either sides of the indent.